India Inc. and globalization: the rise of neo-liberalism and a transnational managerial elite? - Schöttli, Jivanta; Pohlmann, Markus (India review, 2019)
In our paper, we present an empirical study that tests claims regarding the purported impact of economic globalization on business elites, namely that elites become increasingly transnational in their careers and life style and neo-liberal in their action orientations. We draw upon the results of a study that (a) tapped life course data for 100 current top managers in India and (b) implemented a collective mindset analysis using in-depth interviews that were conducted in India with retired and serving senior business managers. Our findings indicate that endogenous institutions have an important and enduring role to play in the shaping of careers, as well as generating embedded cognitive frameworks. Drawing from this exploratory study, we propose a set of hypotheses and a research agenda to argue that socio-cultural mechanisms of selection and socialization must be taken into account in discussions regarding the emergence of a global corporate elite.
Gesehen am 08.07.2019